A New Subclass of Salagean-Type Harmonic Univalent Functions. (4th January 2011) - Al-Shaqsi, Khalifa; Darus, Maslina; Fadipe-Joseph, Olubunmi Abidemi
Abstract : We define and investigate a new subclass of Salagean-type harmonic univalent functions. We obtain coefficient conditions, extreme points, distortion bounds, convolution, and convex combination for the above subclass of harmonic functions.